Penguatan Minat Baca Usia Dini: Psikoedukasi Keterampilan Membaca di TK ‘Aisyiyah G, Yogyakarta - Fitri, Rahma; Khairunnisa, Nadea Zulfa; Aulia, Reva (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This study aimed to examine the effectiveness of psychoeducation in enhancing parents’ understanding and skills in supporting early childhood reading development. The phenomenon underlying this research is the tendency of parents to demand that children be able to read prematurely, without considering the developmental stages of literacy. Such pressure often causes psychological stress for children and may hinder their long-term interest in reading. The participants of this study were parents of students at TK 'Aisyiyah G. The research employed a quasi-experimental method, with the intervention consisting of a psychoeducational program delivered in several sessions covering topics such as understanding early childhood, government policies on early childhood education, children’s psychological development, and strategies to foster reading interest and skills in young children. Data analysis revealed a significant increase in parents’ knowledge and attitudes after the psychoeducation, with the mean score rising from 46.53 (pre-test) to 54.31 (post-test), a difference of 7.78 points, and an effect size of r = 0.80. These findings demonstrate that psychoeducation effectively empowers parents to foster early literacy interest in their children. The study recommends integrating psychoeducational programs into community- and faith-based early childhood education curricula.